Ratio of Monocytes to Lymphocytes in Peripheral Blood in Children Diagnosed with Active Tuberculosis - Ayça Demir; Mine Düzgöl; Nuri Bayram; Ahu Kara; Hurşit Apa; İlker Devrim (Galenos Yayinevi, 2020)
Aim:The ratio of monocytes to lymphocytes (ML) could reflect an immunity to Mycobacterium tuberculosis (TB). The objective of this study was to evaluate the relationship between the ratio of ML and the clinical status of patients with active TB.Materials and Methods:This was a retrospective review of data collected from the clinical database of the Behcet Uz Children's Research Hospital. One hundred thirty-eight patients were diagnosed with pulmonary and extra-pulmonary TB from January 2006 to January 2015. White blood cell count, absolute monocyte and absolute lymphocyte counts, the ML ratio, erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) were compared between extra-pulmonary and pulmonary TB cases. Pre-treatment and after treatment values of the parameters were also compared in both of the groups.Results:A total of 138 patients were diagnosed as having pulmonary or extra-pulmonary TB during the study period. No significant difference between pulmonary and extra-pulmonary TB was present regarding white blood cell count, absolute ML, ESR and CRP (p>0.05). In patients with pulmonary TB and extra-pulmonary TB, a significant decrease in white blood cell count, absolute monocyte count, ESR and CRP values after treatment compared to pretreatment was observed (p<0.05). The ML ratio was not significantly different in the extra-pulmonary TB group (p>0.05) while a significant difference was present between the pre- and post-treatment groups in pulmonary TB (p=0.000).Conclusion:The hematological markers including the ML ratio were found to be more useful for monitoring the response of TB therapy, rather than as a differential diagnosis of pulmonary TB from extra-pulmonary TB.